Keanekaragaman Anopheles dalam Ekosistem Hutan dan Resiko Terjadinya Penularan Malaria di Beberapa Provinsi di Indonesia - Riyani Setiyaningsih; Ary Oksari Yanti S; Lasmiati Lasmiati; Mujiyono Mujiyono; Mega Tyas Prihatin; Widiarti Widiarti; Triwibowo Ambar Garjito (Media Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Forests are ecosystems that can support the existence of malaria vectors. The discovery of vector species in the forest environment will increase malaria transmission in the forest and its surroundings. The provinces of South Sumatra, Central Java, Central Sulawesi, and Papua are some of the provinces in Indonesia that still have forest ecosystems. The aim of the study was to know the diversity of Anopheles species and risk of malaria transmission in forest ecosystems in the provinces of South Sumatra, Central Java, Central Sulawesi, and Papua The sampling of mosquitoes was carried out by using the method of human landing collection, animal bited trap, around cattle collection, resting morning and light trap. Larva surveys are carried out in mosquito breeding place. Detection of plasmodium was done by Polymerase Chain Reaction (PCR) while blood feed analysis was carried out with a blood feed test using the Enzyme-linked immunosorbent assay (ELISA) method. Malaria vector species found in forest ecosystems in Central Java are Anopheles maculatus, Anopheles aconitus, Anopheles vagus, Anopheles balabacensis, and Anopheles subpictus. Malaria vector species in the forest ecosystem in South Sumatra are Anopheles nigerimus and Anopheles maculatus. Anopheles malaria vectors in forest environments in Central Sulawesi are Anopheles flavirostris, Anopheles barbirostris, Anopheles ludlowae, and Anopheles vagus. Anopheles malaria vectors in forest ecosystems in Papua are Anopheles farauti, Anopheles koliensis, Anopheles punctulatus, and Anopheles brancofti. Forest presence is at risk of malaria transmission in the provinces of Central Java, South Sumatra, South Sulawesi and Papua Abstrak Hutan merupakan ekosistem yang dapat mendukung keberadaan vektor malaria. Ditemukannya spesies vektor di lingkungan hutan akan meningkatkan penularan malaria di hutan dan sekitarnya. Provinsi Sumatera Selatan, Jawa Tengah, Sulawesi Tengah, dan Papua merupakan beberapa Provinsi di Indonesia yang masih memiliki ekosistem hutan. Tujuan penelitian adalah mengetahui keanekaragaman spesies Anopheles dan risiko penularan malaria pada ekosistem hutan di Provinsi Sumatera Selatan, Jawa Tengah, Sulawesi Tengah, dan Papua. Pengambilan sampel nyamuk dilakukan dengan menggunakan metode human landing collection, animal bited trap, around cattle collection, resting morning dan light trap. Deteksi plasmodium dilakukan dengan Polymerase Chain Reaction (PCR) sedangan analisa pakan darah dilakukan dengan uji pakan darah metode Enzyme- linked immunosorbent assay (ELISA). Survei jentik dilakukan di tempat-tempat perkembangbiakan nyamuk. Spesies vektor malaria yang ditemukan di ekosistem hutan di Jawa Tengah adalah Anopheles maculatus, Anopheles aconitus, Anopheles vagus, Anopheles balabacensis, dan Anopheles subpictus. Spesies vektor malaria di ekosistem hutan di Sumatera Selatan adalah Anopheles nigerimus dan An. maculatus. Anopheles vektor malaria di lingkungan hutan di Sulawesi Tengah adalah Anopheles flavirostris, Anopheles barbirostris, Anopheles ludlowae dan An. vagus. Anopheles vektor malaria pada ekosistem hutan di Papua adalah Anopheles farauti, Anopheles koliensis, Anopheles punctulatus, dan Anopheles brancofti. Keberadaan hutan berisiko terjadinya penularan malaria di Provinsi Jawa Tengah, Sumatera Selatan, Sulawesi Selatan, dan Papua.